Parental awareness and attitudes towards pediatric dentistry and children’s oral health - Gızem Karagöz Doğan; Yelda Polat; Semanur Özüdoğru (BMC Oral Health)
Abstract Background Parental lack of awareness about oral and dental health has been strongly linked to increased dental caries in children. Furthermore, many parents are not familiar with the pediatric dentistry specialty, resulting in limited knowledge regarding its role in maintaining children’s oral health. Before designing effective educational interventions, understanding parental awareness and attitudes is essential. This cross-sectional study aimed to evaluate parents’ awareness and attitudes regarding their children’s oral and dental health, as well as pediatric dentistry. Methods A 24-question online survey was conducted via Google Forms. Participants included parents with at least one child under 15 years old and without a dental profession. Parents of children with systemic or syndromic conditions were excluded. Data were analyzed using IBM SPSS V23, with statistical significance set at p < 0.05. Results A total of 73.5% of parents were aware of the pediatric dentistry specialty and had taken their children to a pediatric dentist. In cases of pain in primary teeth, 85.5% stated they would consult a dentist, while 10.4% would administer medication and wait. Regarding treatment of primary teeth, 69.5% knew that procedures such as root canal treatments and crowns were possible. About 91.5% paid attention to whether the dentist treating their child was a pediatric dentist. Additionally, 89.6% believed that an infection in a primary tooth could affect the permanent successor. Awareness that pediatric dental treatment could prevent future malocclusion was reported by 79.5%. Moreover, 52.2% were aware that preventive treatments like fluoride and fissure sealants help resist decay; this awareness was significantly higher among parents with undergraduate and postgraduate education (p < 0.001). Similarly, appropriate response to tooth avulsion correlated significantly with higher socioeconomic status (p < 0.001). Conclusion Parental awareness of children’s oral health and pediatric dentistry significantly increases with higher income and education levels. Parents from higher socioeconomic backgrounds demonstrated more informed and preventive approaches. These findings underscore the need for targeted educational programs to raise awareness, especially among socioeconomically disadvantaged groups.